Factors associated with blood pressure and nutritional status among adolescents: a cross-sectional study - Farapti, Farapti; Sari, Afifah Nurma; Sulistyowati, Muji; Aziz, Saidatul Afzan Abdul; Issa, Zuraini Mat; Nor, Norfezah Md (Jurnal Ners, 2024)
Introduction: The association between obesity and hypertension in adolescents necessitates the identification of potential predictors at an early stage. This study aimed to examine the association of sex and place of residence with nutritional status and blood pressure in adolescents aged 10-18 years. Methods: A sample of 198 subjects aged 10-18 years was included in this study. Data on demographic characteristics were collected using a structured questionnaire, whereas nutritional status and blood pressure were measured using standardized measures. Statistical analyses, including the independent t-test, Pearson and Spearman correlation test, and linear regression, were conducted to identify potential risk factors, with statistical significance set at p < 0.05. Results: The study revealed a high prevalence of overweight-obesity (24.7%) and hypertension (11.1%) among the subjects. Significant correlations were observed between body weight, height, age, and blood pressure (p < 0.05). Boys exhibited higher mean body height and Systolic Blood Pressure (SBP) than girls. Nutritional status was positively associated with Body Mass Index (BMI) and blood pressure, with nutritional status emerging as the primary predictor in both private houses and boarding schools (p < 0.05). Furthermore, age at menarche was found to be a predictor of blood pressure in boys, whereas age was a predictor in girls. Conclusions: BMI predicts nutritional status and blood pressure, whereas age and menarche age are crucial factors that depend on sex. Based on these findings, it is critical to manage obesity and hypertension by considering characteristics such as nutritional status, sex, and age